Fertilización Con Potasio Y Fosfitos, Sobre El Rendimiento De Maíz Duro (Zea Mays) En La Zona Subcentral Litoral - Álvaro Lamilla Arana; Eduardo Colina Navarrete; Carlos Castro Arteaga; Danilo Santana Aragone; Guillermo García Vásquez; Oscar Mora Castro; Martha Uvidia Vélez; Joffre León Paredes; Miguel Goyes Cabezas (European Scientific Journal, ESJ, 2018)
The investigation evaluated the effect of fertilizers potásicos with fosfitos on the yield of grain of hard corn (Zea mays L.), in the Property "Santiago", located in the Km 26 way Babahoyo-San Juan, county of Los Ríos. A rehearsal settled down in the hybrid corn DK-7088, measuring the answer from the corn to the application of fertilizers potasic and fhosphite, to determine the dose with more effect on the production. 19 treatments were proven with Chloride of potassium, Sulfate of potassium and Nitrate of potassium, with fhosphite of Calcium, Magnesium and Potassium, more a witness without applications. The used experimental design was complete Blocks at random in three repetitions, the evaluated variables were subjected to the variancia analysis, and the test was applied from Tukey to 95% of probability. The evaluated parameters were: plant height, days to flowering, longitude and ear diameter and yield for hectare. Found increases in grain yield with three treatments, highlighting the treatment with the application of muriate of potash in conjunction with Calcium phosphide (9451,65 kg ha1 ). The results indicate the possibility of increases of more than 49% in relation to the witness (6339 kg ha1 ) where there was applied the treatments.